Transcriptomic analysis reveals differentially expressed genes associated with wool length in rabbit. (1st August 2018) - Zhao, B.; Chen, Y.; Hao, Y.; Yang, N.; Wang, M.; Mei, M.; Wang, J.; Qiu, X.; Wu, X.
Summary: Rabbit fur characteristics are primarily genetically determined traits. We used Illumina high‐throughput sequencing technology to assess gene expression in the skin tissues of rabbits derived from a cross between Wanxi Angora rabbits and Rex rabbits, which exhibit differential characteristics of short and long wool respectively, to investigate molecular mechanisms related to wool length determination. To identify key regulatory genes involved in rabbit wool length, genes that were differentially expressed between the long‐ and short‐wool rabbits based on a P ‐value < 0.05 and log2 |fold change| > 1 were characterized. A total of 798 genes were up‐regulated and 523 were down‐regulated in the long‐wool group compared to expression levels in the short‐wool group, and these genes were annotated with GO terms and KEGG pathways, revealing wool‐development‐related biological functions. The Wnt, Hedgehog and TGF‐ β signaling pathways, which are related to cell proliferation, fibroblast proliferation and hair follicle regulation respectively, were identified. The expression levels of eight genes were validated by RT‐qPCR. In addition, an interaction network was constructed to show the regulatory relationships among the differentially expressed genes. In this study, we found that FGF5, WNT5A, BMP4 and BMP7 showed significant differential expression between the two groups. These transcriptomic profiling results provide comprehensive gene expression information for improving understanding of the molecular mechanisms involved in the growth and development of rabbit wool.